The Incidence and Efficiency Costs of Corporate Taxation When Corporate and Noncorporate Firms Produce the Same Goods. (IMF Working Papers; Working Paper ;, 1988)
One difficulty confronting Harberger's celebrated model of the corporate income tax is how to treat the noncorporate production in primarily corporate sectors and corporate production in primarily noncorporate sectors. This paper presents a two-good model with corporate and noncorporate production of both goods. The incidence of the corporate tax in our Mutual Production Model (MPM) can differ markedly from that in the Harberger Model. The difference between the two models in deadweight loss is also striking, with losses in the MPM over ten times as large as in the Harberger Model.